RANCANG BANGUN RECEIVER SINYAL WI-FI MENGGUNAKAN PERANGKAT NANOSTATION2 LOCO - ., Lydia Lusyanti (Faculty of Engineering, Universitas Tanjungpura, 2016)
Society needs especially college students, access to internet nowdays as a part of life.Hotspot is one of the ways to access the internet through places that provide Wireless Local Area Network technology. This requires a transmitter device,also known as Access Point and receiver device also known as Receiver or Station. Using NanoStation2 Loco as receiver is one effort to receive signal that Access Point at Telecomunication Laboratory transmitted. This project took place at Al-Istiqomah Musholla, Engineering Faculty, Tanjungpura University. The measurements in 166 m² range between the transmitter and receiver, with some parameters, such as signal strength, pingtest, connection quality and pathloss using Friss Propagation model. From measurements, pingtest not always stable, values between 2 ms-34 ms. Connection quality, it’s good for internet access information, almost stable, not much resitences. Pathloss in 166 m² range 84,402 dB, and for signal strength -64,402 dBm. Key words:Access Point, Receiver,Nanostation2 Loco, Pathloss.